2017
DOI: 10.5505/pausbed.2017.37232
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Teachers' Work Engagement And Organizational Commitment

Abstract: Purpose of this study to show the views of teachers, who work in the primary, middle and high school of a town in Turkey, about their work engagement and organizational commitment. Research universe is comprised of teacher who working from Denizli-Kale/Turkey Sample of researches comprises of the absolute amount of universe. In this research data collection tool is comprised from three parts. Researchs show us vigor (high energy level and mental vigor), dedication (inspiration, enthusiasm, pride and high fight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The findings confirmed the hypothesis which means that the higher teachers are committed to their school the higher they will be engaged to their work. The studies conducted on teachers (Çagrı San and Tok, 2017;Pieters and Auanga, 2018) and other samples such as banking employees (Adi and Fithriana, 2020), private and public sector employees (Agyemang and Ofei, 2013), undergraduate students (Babcock-Roberson and Strickland, 2010), airline companies (Li et al, 2010), National Revenue Administration employees (Peplińska et al, 2020), also put forward consistent findings with this study, while food processing plant employees (Gota, 2017) has found that WE is negatively associated with affective commitment. Based on these findings, it can be said that this study contributed to the literature by proving that WE is up to OC.…”
Section: Resultssupporting
confidence: 82%
“…The findings confirmed the hypothesis which means that the higher teachers are committed to their school the higher they will be engaged to their work. The studies conducted on teachers (Çagrı San and Tok, 2017;Pieters and Auanga, 2018) and other samples such as banking employees (Adi and Fithriana, 2020), private and public sector employees (Agyemang and Ofei, 2013), undergraduate students (Babcock-Roberson and Strickland, 2010), airline companies (Li et al, 2010), National Revenue Administration employees (Peplińska et al, 2020), also put forward consistent findings with this study, while food processing plant employees (Gota, 2017) has found that WE is negatively associated with affective commitment. Based on these findings, it can be said that this study contributed to the literature by proving that WE is up to OC.…”
Section: Resultssupporting
confidence: 82%
“…It has been shown that teachers' inner emotions like being optimistic and confident of their teaching abilities will influence their engagement level at work (Minghui et al, 2018). Likewise, research shows that teachers' optimism and commitment can reflect themselves in their occupational performance, satisfaction, problem-solving, and engaggenent (Field and Buitendach, 2012;San and Tok, 2017;Kristiana et al, 2018;Han, 2021a). Other correlates have been approved in the previous studies mentioned earlier in this review article.…”
Section: Correlates Of Teacher Work Engagementmentioning
confidence: 99%
“…Hence job resource predictor should be an integral part of human resources training programme in the organisations. A survey research among teachers who are employed in the basic education levels of schools in Turkey to manifest the views of teachers on work engagement and organisational commitment was undertaken [16].They conducted the study considering the concepts such as vigour, dedication and absorption. Through this study, researchers revealed that vigour, dedication and absorption are three sub dimensions of work engagement and normative feeling, continuity and affectivity are the three sub dimensions of organisational commitment.…”
Section: Page 41mentioning
confidence: 99%